2019
DOI: 10.1186/s12940-019-0482-6
|View full text |Cite
|
Sign up to set email alerts
|

Two-step approach for assessing the health effects of environmental chemical mixtures: application to simulated datasets and real data from the Navajo Birth Cohort Study

Abstract: Background: There is increasing interest in examining the consequences of simultaneous exposures to chemical mixtures. However, a consensus or recommendations on how to appropriately select the statistical approach analyzing the health effects of mixture exposures which best aligns with study goals has not been well established. We recognize the limitations that existing methods have in effectively reducing data dimension and detecting interaction effects when analyzing chemical mixture exposures collected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…This must be interpreted in the context of the health device studied since the public system and the National Health Fund (FONASA) cover the population with the lowest income in Chile 34 . Regarding the seasonality observed in the requirement for speech therapy in the cohort, the literature indicates that there are environmental determinants that may influence the behavior of patients seeking medical or rehabilitation services 35,36 due to respiratory exacerbations, heart attacks, or cerebrovascular disease, among others [37][38][39] . However, there is no evidence related to the association between these factors and the provision of care by speech therapists, which is considered a precedent for future research.…”
Section: Resultsmentioning
confidence: 99%
“…This must be interpreted in the context of the health device studied since the public system and the National Health Fund (FONASA) cover the population with the lowest income in Chile 34 . Regarding the seasonality observed in the requirement for speech therapy in the cohort, the literature indicates that there are environmental determinants that may influence the behavior of patients seeking medical or rehabilitation services 35,36 due to respiratory exacerbations, heart attacks, or cerebrovascular disease, among others [37][38][39] . However, there is no evidence related to the association between these factors and the provision of care by speech therapists, which is considered a precedent for future research.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have used random forests for dimension reduction and LASSO for subsequent modeling. 72 In contrast, we used LASSO models for preprocessing, as variable selection in random forest models may be unstable when low-relevance or correlated variables are included, and because we were interested in identifying provision combinations—a task better suited to random forest rather than LASSO approaches. Finally, because our analyses included all provisions simultaneously—so that we could systematically compare provisions in terms of predictive relevance—we could not incorporate time lags beyond the 6-month sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of applying dimension reduction and determining the strength of an association between a variable that includes interaction terms, Li L. [10] presented a double step method consolidating Random forest and ALasso. They concluded that the proposed method outperformed the other techniques by producing a parsimonious model.…”
Section: Zou and Hastiementioning
confidence: 99%